A qualitative study of parents support group and skills training for parents of children with autism spectrum disorder - Ahmad Basri, Nadzirah; Mohd Taib, Nasehah; Najib Mohammad, Hanisa Begam (2019)
Backgrounds Caring for an autism spectrum disorder child requires high emotional demand and commitment, often leading to sacrifices by the parents, such as leaving work and distancing from their friends. Follow-up services and continued support for the parents is a necessary component to help them adapt and meet their and their children’s needs. This study aims to identify the extent of support provided by a three-session, co-facilitated, support group and skills-training for parents with an autism child held at a Medical Centre in the East Coast of Malaysia. Methods Qualitative data collection was carried out through individual interviews with parents of children with autism who participated in at least two out of the three sessions of the support group and skills training. Results The following themes were identified: acceptance, social support, spiritual connection, child-parent interaction and self-care. Some participants shared that communication with their spouses have improved after joining the support group. Some felt soothed to hear of others being in the same situation as them, while others felt they were better able to tolerate behavioral problems manifested by their child after the skills workshop. Parents indicated that the support groups assisted them in acquiring advocacy skills and provided good emotional and informational support. This study was important because parents of children with autism experience greater stress than parents of typical children and many parents felt alone in their journey of bringing up their autistic child that they needed to obtain advocacy skills and emotional support to support them to give the best intervention for their child.